2010
DOI: 10.3168/jds.2009-2474
|View full text |Cite
|
Sign up to set email alerts
|

Survival and replication of Mycoplasma species in recycled bedding sand and association with mastitis on dairy farms in Utah

Abstract: Mycoplasma spp., usually Mycoplasma bovis, are important bovine pathogens that can cause mastitis, metritis, pneumonia, and arthritis. The currently documented routes of transmission of Mycoplasma spp. are through contaminated milking equipment and by direct animal contact. The existence of environmental sources for Mycoplasma spp. and their role in transmission and clinical disease is poorly characterized. Mycoplasma spp. (confirmed as M. bovis in 2 of 4 samples tested using PCR) was found in recycled bedding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…Materials studied were those that could be typically found on dairies including sponges, stainless steel, wood, rubber, glass, and water. Justice-Allen and coworkers 45 in Utah discovered that Mycoplasma could live for up to 8 months in a sand pile. The sand originated from a herd with an outbreak of Mycoplasma mastitis.…”
Section: Transmissionmentioning
confidence: 98%
See 1 more Smart Citation
“…Materials studied were those that could be typically found on dairies including sponges, stainless steel, wood, rubber, glass, and water. Justice-Allen and coworkers 45 in Utah discovered that Mycoplasma could live for up to 8 months in a sand pile. The sand originated from a herd with an outbreak of Mycoplasma mastitis.…”
Section: Transmissionmentioning
confidence: 98%
“…Mycoplasma was also isolated in sand from 2 other dairies. The authors 45 suggested that sand could be a reservoir for Mycoplasma mastitis. However, in a separate investigation where there appeared to be a link between sand bedding and a clinical mastitis outbreak, it was found that the strains of Mycoplasma sp in the bedding had a completely different DNA fingerprint than those causing mastitis (Fox and Corbett, unpublished data, 2008).…”
Section: Transmissionmentioning
confidence: 99%
“…Even familiar zoonotic pathogens with non‐environmental routes of exposure can show surprising and unexpected patterns of environmental persistence. For example, recent work has confirmed that Mycoplasma bovis , a bacterial pathogen associated with mastitis in cattle and bison ( Bison bison ), can persist for long periods and possibly replicate, most likely through the formation of biofilms associated with gram‐negative bacteria, in sandy soil used as cattle bedding under certain moisture conditions (Justice‐Allen et al ., ). Similarly, plague ( Yersinia pestis ), conventionally studied as a vector‐borne disease, recently has been shown to persist in the soil for weeks – although the importance of this to the ecology and epidemiology of plague is still controversial (Lowell et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In Europe, M. bovis is believed to be responsible for 25-33% of outbreaks of calf pneumonia. This Mycoplasma species is also associated with the diseases of bulls' genital tract (seminal vesiculitis, epidydimitis, orchitis) and reproductive disorders of cows as well (mastitis, metritis, salpingitis and abortion) (Nicholas and Ayling 2003, Justice-Allen et al 2010, Punyapornwithaya et al 2010.…”
Section: Introductionmentioning
confidence: 99%